Mitochondrial genome assembly and population genetics of the common smoothhound shark, Mustelus mustelus - Hull, Kelvin Lloyd (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.